Exercise Reduces the Number of Overall and Major Osteoporotic Fractures in Adults. Does Supervision Make a Difference? Systematic Review and Meta‐Analysis. (9th September 2022) - Hoffmann, Isabelle; Shojaa, Mahdieh; Kohl, Matthias; von Stengel, Simon; Becker, Clemens; Gosch, Markus; Jakob, Franz; Kerschan‐Schindl, Katharina; Kladny, Bernd; Clausen, Jürgen; Lange, Uwe; Middeldorf, Stefan; et al.
ABSTRACT: The purpose of this systematic review and meta‐analysis (PROSPERO ID: CRD42021250467) was to evaluate the effects of exercise on low‐trauma overall and major osteoporotic fractures (hip, spine, forearm, or humerus fractures) and to determine the corresponding effect of supervision of the exercise program. Our systematic search of six literature databases according to the PRISMA guideline was conducted from January 1, 2013 (ie, date of our last search) to May 22, 2021, and included controlled clinical exercise trials with (i) individuals aged ≥45 years, (ii) cohorts without therapies/diseases related to fractures, (iii) observation periods of ≥3 months, and (iv) the number of low‐trauma fractures listed separately for the exercise (EG) and control (CG) groups. We included 20 intervention studies with 21 EGs and 20 CGs comprising a pooled number of participant‐years of n = 11.836 in the EG and n = 11.275 in the CG. The mixed‐effects conditional Poisson regression revealed significant effects of exercise on low‐trauma overall incidence (rate) ratio (IR 0.67, 95% confidence interval [95% CI] 0.51–0.87) and major osteoporotic fractures IR (0.69, 95% CI 0.52–0.92). Heterogeneity between the trials was moderate for low‐trauma overall (I2 = 40%) and negligible (I2 < 1%) for major osteoporotic fractures. Supervision of the exercise program plays a significant role in the reductions of overall and major osteoporotic fractures with IR about twice as favorable in the predominately supervised (IR 0.44; 95% CI 0.27–0.73 and 0.38; 0.19–0.76) versus the predominately non‐supervised exercise trials (IR 0.83; 95% CI 0.60–1.14 and 0.82; 0.64–1.05). In summary, the present study provides evidence for the positive effect of exercise on low‐trauma overall and major osteoporotic fractures in middle aged to older adults. Supervision of the exercise program is a crucial aspect in exercise programs on fracture reduction. Thus, home‐based exercise protocols should increasingly implement online classes to ensure widely consistent supervision and monitoring of the exercise program. © 2022 The Authors. Journal of Bone and Mineral Research published by Wiley Periodicals LLC on behalf of American Society for Bone and Mineral Research (ASBMR).